Luxembourg : 2016 Article IV Consultation-Press Release; Staff Report; Informational Annex; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses growth prospects and downside risks of Luxembourg's economy. Luxembourg's small open economy plays a pivotal role in intermediating global capital flows. Deep-rooted traditions of fiscal prudence, business-friendly regulation, a skilled labor force, and low and predictable taxes have made Luxembourg a global financial center, home of multinational companies, and one of the richest countries in the European Union (EU). However, financial market stress could affect Luxembourg's performance. In case of severe external shocks, unraveling financial exposures could prompt dislocations in markets or institutions beyond the scope of the national authorities. The European Banking Union and EU financial regulations frameworks are particularly positive for Luxembourg.